Palatability Evaluation of Nuggets from Spent Laying Hen Meat Using Arrowroot Flour Substitution as Alternative Filler - Mahmudah, Nur Aini; Zubaidah, Siti; Sriani; Mardiana, Nur Agustin (Sriwijaya FoodTech Journal, 2025)
This study aims to evaluate the effect of arrowroot flour substitution on the sensory quality and palatability of chicken meat nuggets. Four nugget formulations were developed based on the proportion of wheat flour and arrowroot flour as fillers, namely 100% wheat flour (control/code 501), 90:10 (code 105), 80:20 (code 201), and 70:30 (code 315). Sensory evaluation was conducted by 29 semi-trained panelists on the attributes of color, aroma, taste, texture, and overall quality. The results showed that an increase in cassava flour substitution gradually affected a decrease in taste and texture quality, particularly in formulations 201 and 315. Formulation 105 achieved the highest scores for texture and overall, and was evaluated as having a dominant chicken and spice flavor by 44.8% of the panelists. Conversely, formulation 315 showed a decrease in palatability, with an increase in the perception of a dominant flour flavor and a denser texture. Arrowroot flour was assessed as having potential as a local filler alternative, but its use should be limited to avoid reducing consumer preference. Thus, substituting 10% arrowroot flour is the optimal formulation for producing chicken nuggets that are preferred by panelists in terms of color, taste, texture, and overall palatability.